Nierozwiązana zagadka Jsydora Szykiera z Szadka i to, czego możemy się z niej nauczyć - Klauzińska, Kamila; Polkowski, Tomasz Krzysztof (Biuletyn Szadkowski, 2013)
This paper presents the results of research conducted on the book Tiḳun lei Szawuot we-Haszana raba, which was printed in 1844 in Warszawa, and today belongs to the collection of the Museum of the History of Zduńska Wola. A stamp inside of the book, stating "Jsydor Szykier, SZADEK", was the starting point of the research and of this paper. The authors have attempted to find out how this book, which belonged to a resident of Szadek, made its way to Zduńska Wola, and at the same time reconstruct a chapter in the history of the Szykier family. lt is also a great opportunity to tell about Jewish genealogy customs. The authors have conducted their research in the National Archives in Sieradz and Łódź, and used selected research findings of Klauzińska's PhD dissertation, based on the answers of a large sample of Jewish genealogists.